Effect of iron additives on the thermal degradation of coal from the Shubarkol deposit - Baikenov, M.I.; Ivannikova, A.V.; Baikenova, G.G.; Khalikova, Z.S.; Kochegina, E.V.; Rakhimzhanova, N.Zh.; Karimova, A.B.; Kezdikbaeva, A.T. (Allerton Press, 2016)
The kinetic parameters of the thermal degradation of coal in a temperature range of 32–458°C without additives and in the presence of nanosized iron powder as a catalyst were calculated based on thermogravimetric analysis data. The rate constants and activation energies of the first and second steps of thermal degradation processes were determined. The influence of the catalytic additive on the value of activation energy was found. The results of the thermogravimetric analysis can be used in a study of thermocatalytic modification processes for the hydrogenation of fossil coals.